A hepatitis B virus flare that led to hepatic decompensation and liver transplantation in a pregnant woman with chronic hepatitis B: a rare case report and literature review - Chih-Hsiang Yin; Chia-Ching Chang; Yi-Liang Lee; Shou-En Wu; Yi-Hsin Lin; Paul Ivan Kato; Chuang-Yen Huang (Clinical and Experimental Obstetrics & Gynecology)
Background: Acute viral hepatitis is the most common cause of jaundice during pregnancy. Distinct immunological changes during pregnancy and the postpartum period are possible crucial factors associated with flares of chronic hepatitis B. Case: We present the case of a healthy pregnant hepatitis B virus (HBV) carrier at 38 weeks of gestation. She underwent an emergent cesarean section due to acute hepatitis B flare, and ultimately underwent liver transplantation due to a decompensating liver based on an estimated Model for End-Stage Liver Disease score. Conclusions: For pregnant HBsAg positive women, close monitoring with serum HBV-DNA and spartate transaminase (AST)/alanine transaminase (ALT) levels every 3 months is highly recommended. According to the latest guidelines, prenatal antiviral therapy, postpartum HBV vaccination, and hepatitis B immunoglobulin should be administered to prevent mother-to-child transmission.